The shifting of moral hazard in consumer credit : does the National Credit Amendment Act 19 of 2014 tip the scales in favour of debtor? - Brits, Reghard (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2017.